2017
DOI: 10.1002/jor.23642
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐engineered tendon constructs for rotator cuff repair in sheep

Abstract: Current rotator cuff repair commonly involves the use of single or double row suture techniques, and despite successful outcomes, failure rates continue to range from 20 to 95%. Failure to regenerate native biomechanical properties at the enthesis is thought to contribute to failure rates. Thus, the need for technologies that improve structural healing of the enthesis after rotator cuff repair is imperative. To address this issue, our lab has previously demonstrated enthesis regeneration using a tissue-enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The sheep infraspinatus tendon acute transection/repair model was used as previous studies have demonstrated that it is a good analog for the human supraspinatus tendon. 14,17,18,[31][32][33][34][35]40,41 Using an open approach, the infraspinatus tendon was sharply detached from the humeral footprint followed by removal of any remaining soft tissue from the footprint by a bone burr. Repair or reattachment of the transected tendon was immediately performed using a total of two 2.7-mm suture anchors (BioWick SureLock W Suture Anchor; Zimmer-Biomet, Warsaw, IN, USA) with a PLGA scaffold (ie, Treatment group) ( Fig.…”
Section: Animal Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…The sheep infraspinatus tendon acute transection/repair model was used as previous studies have demonstrated that it is a good analog for the human supraspinatus tendon. 14,17,18,[31][32][33][34][35]40,41 Using an open approach, the infraspinatus tendon was sharply detached from the humeral footprint followed by removal of any remaining soft tissue from the footprint by a bone burr. Repair or reattachment of the transected tendon was immediately performed using a total of two 2.7-mm suture anchors (BioWick SureLock W Suture Anchor; Zimmer-Biomet, Warsaw, IN, USA) with a PLGA scaffold (ie, Treatment group) ( Fig.…”
Section: Animal Proceduresmentioning
confidence: 99%
“…Various techniques have been employed to improve interface healing, including bone marrow venting; cellular therapies (mesenchymal stem cells); and xenograft, allograft, or acellular scaffolds. 27,29,32,36,41 Bone marrow vents have shown promise in improving the bone-tissue interface healing of many soft tissue injuries by allowing autologous marrow-derived cells to reach the repair site. 9,37 Bone marrow venting is a comparatively expeditious surgical procedure, has no issue of cellular incompatibility, and may be accomplished through vented tissue anchors or through separate bone puncture holes.…”
mentioning
confidence: 99%
See 3 more Smart Citations